Converting Relational Database into Temporal Database - Indra Kurniawan, Yogiek; Ayu Laksitowening, Kusuma; Romadhony, Ade; Fachrie, Muhammad; Aryo Anggoro, Dimas (International Journal of Engineering and Technology, 2019)
In this paper, perform the implementation of temporal database which take into account the historical aspects of data and how to convert relational database into temporal database. After performing the implementation, an analysis of queries is done in accessing each data that takes into account the historical aspects of data, for Data Definition Language (DDL), Data Manipulation Language (DML) and queries for retrieve data. After the analysis, it is concluded that the use of queries for temporal database can be done on the relational database with some adjustments. In addition, temporal databases have advantages in terms of storage usage and response time for DDL and DML queries, but for response time in query retrieve data takes longer than relational database.Â Â